2021
DOI: 10.1111/anae.15488
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of bilateral erector spinae plane block vs. no block for thoracolumbar decompressive spinal surgery

Abstract: Major spinal surgery causes significant postoperative pain. We tested the efficacy and safety of bilateral erector spinae block on quality of recovery and pain after thoracolumbar decompression. We randomly allocated 60 adults to standard care or erector spinae block. Erector spinae block improved the mean (SD) quality of recovery-15 score at 24 postoperative hours, from 119 (20) to 132 ( 14), an increase (95%CI) of 13 (4-22), p = 0.0044. Median (IQR [range]) comprehensive complication index was 1 (0-3 [0-5]) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 29 publications
(45 reference statements)
1
30
0
Order By: Relevance
“…Out of the 52 RCTs, 11 were about breast surgeries, 24–26 , 31 , 36 , 38 , 39 , 47 , 48 , 54 , 64 15 were about orthopedic surgeries, 10 , 11 , 21–23 , 27 , 28 , 32 , 33 , 50 , 52 , 53 , 56 , 57 , 60 5 were about thoracoscopic surgeries, 12 , 25 , 34 , 58 , 59 6 were about cholecystectomy, 29 , 30 , 41 , 45 , 63 , 65 6 were about nephrolithotomy, 37 , 44 , 49 , 61 , 62 , 68 2 were about cardiac surgeries, 14 , 42 and 7 were others. 40 , 43 , 46 , 51 , 55 , 66 , 67 The characteristics of enrolled 52 studies were listed in the Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 52 RCTs, 11 were about breast surgeries, 24–26 , 31 , 36 , 38 , 39 , 47 , 48 , 54 , 64 15 were about orthopedic surgeries, 10 , 11 , 21–23 , 27 , 28 , 32 , 33 , 50 , 52 , 53 , 56 , 57 , 60 5 were about thoracoscopic surgeries, 12 , 25 , 34 , 58 , 59 6 were about cholecystectomy, 29 , 30 , 41 , 45 , 63 , 65 6 were about nephrolithotomy, 37 , 44 , 49 , 61 , 62 , 68 2 were about cardiac surgeries, 14 , 42 and 7 were others. 40 , 43 , 46 , 51 , 55 , 66 , 67 The characteristics of enrolled 52 studies were listed in the Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…There were 15 RCTs (875 patients) evaluated the effect of ESPB in orthopedic surgery, 10 , 11 , 21–23 , 27 , 28 , 32 , 33 , 50 , 52 , 53 , 56 , 57 , 60 which reported opioid consumption in postoperative 24 h. Meta-analysis demonstrated that compared to the non-block groups or the sham block, ESPB significantly reduced 24-hour opioid consumption (−9.97 mg; 95% CI: −12.58 to −7.37; p < 0.001; I 2 = 98%) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The ESP block has become progressively more popular in recent times, and its use has been reported in a range of thoracic, spinal and abdominal surgeries. [18][19][20][21] Single shot truncal regional anaesthesia techniques such as paravertebral and ESP blocks have shown to contribute to post-operative analgesia after MITS but they are restricted by the limited duration of analgesia, which extends to no more than 12 hours in duration. 6,10 Catheter techniques offer opportunities of increased exibility and prolonged analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Title and abstract screening eliminated 2,101 citations. Out of the remaining 63 studies, 50 were excluded after full-text review, leaving 13 studies for inclusion (Table 1) (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). All the included studies were RCTs.…”
Section: Selection Of Articles Study Characteristics and Study Qualitymentioning
confidence: 99%